Strengthening the International Monetary System : Taking Stock and Looking Ahead. (Policy Papers; Policy Paper ;, 2011)
The current IMS has survived for over forty years, underpinning strong growth in GDP and in the international exchange of goods and capital, one of its core objectives. As a result, interdependence among the world's economies has grown dramatically, making the existence of a sound system ever more important. At the same time, the system has exhibited many symptoms of instability-frequent crises, persistent current account imbalances and exchange rate misalignments, volatile capital flows and currencies, and unprecedentedly large reserve accumulation. These symptoms have come to a head since the 2008 crisis and brought renewed international momentum to the idea of attempting to reform the IMS. Yet the debate so far suggests little consensus on the underlying problems, let alone on the solutions. This paper identifies four root causes to these problems: inadequate global adjustment mechanisms to prevent inconsistent or imprudent policies among systemic countries; lack a comprehensive oversight framework for growing cross-border capital flows, covering both source and recipient countries; inadequate systemic liquidity provision mechanisms; and structural challenges in the supply of safe assets.